Agronomic response and incidence of Mildiu in turnip crops (Brassica napus L.) with the inoculation of Azotobacter sp and Azospirillum brasilense - Torres-Torres, Euro Ignacio (2022)
The benefits of using beneficial bacteria in agriculture are numerous, among them, it helps to improve the yield of crops, inhibits the development of phytopathogens, induces defensive responses in plants and increases their protection against microorganisms, etc. The main objective of this investigation was to evaluate the effect of different bacterial concentrations of Azotobacter sp and Azospirillum brasilense on the growth, development and control of Mildius caused by Peronospora brassicae Gaumann. The experimental design that was used in the investigation was a complete design at random with 8 treatments untest experimental and four repetitions. The turnip seeds were soaked for 2 hours in each of the treatments before planting afterwards, the treatments were applied at 10, 20 and 30 days. To see the differences between the treatments, Tukey's test was implemented (p=< 0.05). The results determined that seeds soaked in bacteria did not represent significant differences (p>=0.05) in the plant emergence parameter. With regard to growth and production parameters such as: height of the plant, length and diameter of the root, fresh and dry biomass of the seedlings and radicles and yield, it was observed that the treatments inoculated with Azotobacter sp and Azospirillum brasilense were one concentration of 1x109 CFU mL-1 presented the best averages if they are significant (p=< 0.05) with respect to the experimental test. The incidence of Mildiu was lower in treatments with the application of Azospirillum brasilense in doses of 1x109 CFU mL-1.